On the physics of dispersive electron transport characteristics in SnO2 nanoparticle-based dye sensitized solar cells. (1st March 2018) - Ashok, Aditya; Vijayaraghavan, S N; Unni, Gautam E; Nair, Shantikumar V; Shanmugam, Mariyappan
Abstract: The present study elucidates dispersive electron transport mediated by surface states in tin oxide (SnO2 ) nanoparticle-based dye sensitized solar cells (DSSCs). Transmission electron microscopic studies on SnO2 show a distribution of ∼10 nm particles exhibiting (111) crystal planes with inter-planar spacing of 0.28 nm. The dispersive transport, experienced by photo-generated charge carriers in the bulk of SnO2, is observed to be imposed by trapping and de-trapping processes via SnO2 surface states present close to the band edge. The DSSC exhibits 50% difference in performance observed between the forward (4%) and reverse (6%) scans due to the dispersive transport characteristics of the charge carriers in the bulk of the SnO2 . The photo-generated charge carriers are captured and released by the SnO2 surface states that are close to the conduction band-edge resulting in a very significant variation; this is confirmed by the hysteresis observed in the forward and reverse scan current–voltage measurements under AM1.5 illumination. The hysteresis behavior assures that the charge carriers are accumulated in the bulk of electron acceptor due to the trapping, and released by de-trapping mediated by surface states observed during the forward and reverse scan measurements.